CONTUMACIOUS LEG ULCER, AN UNCOMMON PRESENTATION IN NEWLY DIAGNOSED E/BETA THALASSEMIA - Dr Rashmi Verma; Dr Shaifali Bansal; Dr Ashraf Malik; Sourabh Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Beta-thalassemia are a group of hereditary blood disorders characterized by anomalies in the synthesis of the beta chains of haemoglobin resulting in variable phenotypes ranging from severe anaemia to clinically asymptomatic individuals. Leg ulcers may develop in patients with sickle cell anaemia and other haemolytic disorders, as a result of red blood cell (RBC) deformability and endothelial changes. Following case report highlights undiagnosed E/beta thalassemia patient having being treated as a chronic non healing ulcer over the medial aspect of left leg above medial malleolus